The heterozygous R155C VCP mutation: Toxic in humans! Harmless in mice? - Clemen, Christoph S.; Winter, Lilli; Strucksberg, Karl-Heinz; Berwanger, Carolin; Türk, Matthias; Kornblum, Cornelia; Florin, Alexandra; Aguilar-Pimentel, Juan Antonio; Amarie, Oana Veronica; Becker, Lore; Garrett, Lillian; Hans, Wolfgang; et al. (Biochemical and Biophysical Research Communications, 2018)
Heterozygous missense mutations in the human VCP gene cause inclusion body myopathy associated with Paget disease of bone and fronto-temporal dementia (IBMPFD) and amyotrophic lateral sclerosis (ALS). The exact molecular mechanisms by which VCP mutations cause disease manifestation in different tissues are incompletely understood. In the present study, we report the comprehensive analysis of a newly generated R155C VCP knock-in mouse model, which expresses the ortholog of the second most frequently occurring human pathogenic VCP mutation. Heterozygous R155C VCP knock-in mice showed decreased plasma lactate, serum albumin and total protein concentrations, platelet numbers, and liver to body weight ratios, and increased oxygen consumption and CD8+/Ly6C + T-cell fractions, but none of the typical human IBMPFD or ALS pathologies. Breeding of heterozygous mice did not yield in the generation of homozygous R155C VCP knock-in animals. Immunoblotting showed identical total VCP protein levels in human IBMPFD and murine R155C VCP knock-in tissues as compared to wild-type controls. However, while in human IBMPFD skeletal muscle tissue 70% of the total VCP mRNA was derived from the mutant allele, in R155C VCP knock-in mice only 5% and 7% mutant mRNA were detected in skeletal muscle and brain tissue, respectively. The lack of any obvious IBMPFD or ALS pathology could thus be a consequence of the very low expression of mutant VCP. We conclude that the increased and decreased fractions of the R155C mutant VCP mRNA in man and mice, respectively, are due to missense mutation-induced, divergent alterations in the biological half-life of the human and murine mutant mRNAs. Furthermore, our work suggests that therapy approaches lowering the expression of the mutant VCP mRNA below a critical threshold may ameliorate the intrinsic disease pathology.
EVALuna2:36583